Elaboración de un software multimedia para satisfacer la necesidad de los conocimientos sobre la evolución del sistema operativo Windows en los estudiantes del 8vo año de educación básica del colegio nacional mixto “San Luis” durante el periodo 2009 – 2010 provincia Bolívar, cantón Guaranda. - López Armijo, Nelly Janeth (2010)
The present grade work carries out it according to one of the necessities of the students in which we outline the following hypothesis. One will be able to satisfy the necessities of the knowledge on the evolution of the Operating system Windows elaborating a Software Multimedia like support in the process learning of the students. We outline the topic, the antecedents, we look for solution to the problem, we justify for that we carry out and we think about our objectives in the project, variables. The development of the chart of contents, showing the order of the topic and subthemes facilitating the information. The present work is specified in the following way. Chapter I the summary of all the information of scientific theory, the conceptual theory, and the theory referential of the Institution where we carry out the investigation. Chapter II the methodological strategies. The purpose, for the level, for the investigation place, the techniques and instruments for the obtaining of data, the design for the temporary dimension, the universe and sample, the prosecution of data and the methods that we use. Chapter III the analysis and interpretation of results, we check the hypothesis, we give our conclusions and recommendations. Chapter IV the proposal of the project, I title, introduction, objectives, development, evidences of the application of the proposal and the results of the application. Bibliography of all the information obtained grade work and annexes presently.